Fatal HLH in patients with X-linked lymphoproliferative disease 1 due to a novel variant in SH2D1A: case report - Boyarchuk, Oksana; Volokha, Alla; Yarema, Nataliia; Dyvoniak, Olga; Tomashivska, Tetyana; Shymanska, Ivanna; Makukh, Halyna; Walter, Jolan E. (Frontiers in Immunology, 2025)
IntroductionX-linked lymphoproliferative disease type 1 (XLP1) is an inborn error of immunity (IEI) caused by pathogenic variants in the SH2D1A gene, leading to severe immune dysregulation, often triggered by Epstein-Barr virus (EBV) infection. Hemophagocytic lymphohistiocytosis (HLH) is one of the most severe manifestations of XLP1 with high mortality.ObjectivePresent a clinical case of fatal HLH associated with a novel SH2D1A variant, highlighting the variability of clinical presentation and the potential role of co-infections.MethodsWe analyzed clinical and laboratory data of three brothers who died from HLH in early age. Genetic evaluation was performed using a 576-gene panel for IEI (Veritas, Spain, supported by the Jeffrey Modell Foundation). Alive siblings and parents were tested in Scientific Medical Genetic Center LeoGENE, Ukraine.ResultsA 1-year-old boy was admitted with a persistent 4-day fever and clinical signs of hepatosplenomegaly, anemia, neutropenia, hypertransaminasemia, and hypoproteinemia. Immunophenotyping revealed decreased CD4, increased CD8 T cells, reduced NK cell counts, and elevated immunoglobulin levels. This patient demonstrated high EBV viremia and positive serological markers for SARS-CoV-2. Despite intensive treatment, HLH progressed rapidly, leading to fatality within 35 days. Genetic testing identified a novel, likely pathogenic hemizygous SH2D1A variant, c.175delC (p.Thr59Glnfs*22), not previously reported in affected individuals or the gnomAD database. Family history shows that two older male siblings died at 11 months and 1 year 9 months from a rapidly developed disease presented by fever, hepatosplenomegaly, dermatitis, enterocolitis, anemia, thrombocytopenia, and hypertransaminasemia. The second affected sibling tested positive for EBV serology. The family also included a healthy sister and brother, both with positive EBV serology (IgG) but no detectable viremia. Carrier testing confirmed that the mother and sister are heterozygous carriers, while two male siblings (one of them was born 1 month ago) are unaffected.ConclusionWe identified a novel SH2D1A variant associated with fatal HLH in XLP1. Our findings highlight the importance of early genetic diagnosis before EBV exposure to improve patient outcomes. The potential role of co-infections, including SARS-CoV-2, in triggering HLH in XLP1 remains an area for further investigation.